Case Report: Combination Therapy of Electrocautery and Zinc Sulfate in Perianal Giant Condylomata Acuminata with Human Immunodeficiency Virus (HIV) - Lita Setyowatie; Rizky Devitasari (Asian Journal of Health Research, 2023)
Introduction: Giant Condylomata Acuminata (GCA) or Buschke-Lowenstein tumours are rare variations of anogenital warts. Immunocompromising conditions are closely related to the development of GCA. There is no standard therapy in the management of GCA. Its large size allows malignant transformation and high recurrence. Case Presentation: A male, 26 years old, with a complaint of wart in the anal in the last 11 months. The lump was getting bigger and sometimes bleed. The patient had been diagnosed with HIV 1 year ago and had received routine antiretroviral therapy (ARV). On physical examination of the perianal region showed stalked vegetation which was hypopigmented, partly erythema, verrucous surface, in the form of cauliflower, multiple, measuring 1.5x1.5x4 cm. A positive acetowhite test and histopathological examination showed condylomata acuminata. Patients were given combination electrocautery therapy and zinc sulfate 5-10 mg/kg/day for 2 months. Significant improvement appears and GCA disappears entirely. Conclusion: Electrocautery and zinc sulfate as an immunomodulator can be considered as a treatment of GCA with HIV because they can work synergistically to achieve resolution of the lesion and prevent recurrence of GCA.